Pengaruh Citra Merek, Kualitas Produk dan Harga Terhadap Minat Beli Konsumen Produk Sari Roti - Mita Ananda Fairuz; Siti Nurjanah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This research was conducted with the aim of knowing the effect of brand image, product quality, price on purchase intention partially. The research method used is a quantitative method with nonprobability sampling technique with purposive sampling method to determine the research sample. The number of samples used was 304 respondents with the Heir method. Hypothesis testing used in this study includes the t test, f test, determination test, and multiple linear regression analysis. The results of this study indicate that 1) brand image has a significant effect on purchase intention; 2) product quality has a significant effect on purchase intention; 3) price has a significant effect on purchase intention.